Inactivation of Resistant Mycobacteria mucogenicum in Water： Chlorine Resistance and Mechanism Analysis - CHEN, Yu Qiao; CHEN, Chao; ZHANG, Xiao Jian; ZHENG, Qi; LIU, Yuan Yuan (Biomedical and environmental sciences, 2012)
Objective To better understand the mechanism of chlorine resistance of mycobacteria and evaluate the efficiency of various disinfection processes.Methods Inactivation experiments of one strain Mycobacteria mucogenicum,isolated from a drinking water distribution system in South China were conducted with various chlorine disinfectants.Inactivation efficiency and disinfectant residual,as well as the formation of organic chloramines,were measured during the experiments.Results This strain of M.mucogenicum showed high resistance to chlorine.The CT values of 99.9% inactivation by free chlorine,monochloramine and chlorine dioxide were detected as 29.6±1.46,170±6.16,and 10.9±1.55 min（mg/L） respectively,indicating that chlorine dioxide exhibited significantly higher efficiency than free chlorine and monochloramine.It was also found that M.mucogenicum reacted with chlorine disinfectants more slowly than S.aureus,but consumed more chlorine disinfectants during longer time of contact.Lipid analysis of the cell construction revealed that 95.7% of cell membrane lipid of M.mucogenicum was composed of saturated long chain fatty acids.Saturated fatty acids were regarded as more stable and more hydrophilic which enabled the cell membrane to prevent the diffusion of chlorine.Conclusion It was concluded that different compositions of cell membrane might endow M.mucogenicum with a higher chlorine resistance.